GilingOBar: Inovasi Aplikasi Penggilingan Padi Berbasis GIS untuk efisiensi Rantai Pasok di Jawa Tengah - Dewangga, Kusuma; Widhiyanti, Kathryn (Jurnal Dinamika Ekonomi Pembangunan, 2025)
Central Java Province accounts for 21% of national rice production (BPS, 2024), but 34.5% of farmers still face a price disparity of Rp1,500/kg between grain and rice (Ministry of Agriculture, 2024). In addition, the supply chain is not yet efficient, with a waiting time of 3-4 days and post-harvest losses reaching 12.3% due to manual systems. The research developed GilingOBar, a cloud-based GIS application to integrate farmers with rice milling centers. This application introduces the concept of Digital Grain Pooling, which combines the supply of farmers in one area with the support of the Smart Routing System to reduce transportation costs. Market transparency is also realized through real-time data on milling rates and grain and rice prices. The season and weather prediction features help farmers determine the right milling time so that post-harvest losses can be reduced. The research method combines Agile Development and Action Research. Agile supports the development of the application in stages with direct feedback from farmers and millers, while Action Research ensures the technology is truly relevant to the socio-economic conditions of traditional farming. The findings of this study align with the objectives of the Digital Agriculture Roadmap 2024–2029, particularly the target of digitizing 50% of agribusiness transactions. Beyond supporting this policy direction, the proposed GilingOBar platform introduces a novel technology-driven business model that applies shared economy principles to the post-harvest rice supply chain. Unlike existing digital initiatives, GilingOBar integrates real-time data, digital coordination, and community-based logistics into a single system. This innovation contributes to higher farm incomes, improved supply chain efficiency, greater price transparency, reduced post-harvest losses, and strengthened empowerment of agricultural communities.